Use of encapsulated stem cells to overcome the bottleneck of cell availability for cell therapy approaches - Freimark, Denise; Pino-Grace, Pablo; Pohl, Sebastian; Weber, Christian; Wallrapp, Christine; Geigle, Peter; Portner, Ralf; Czermak, Peter (My University, 2010)
Nowadays cell-based therapy is rarely in clinical practice because of the availability of appropriate cells. To apply cells therapeutically, they may not cause any immune response wherefore up to now mainly autologous cells were used. The amount of vital cells in patients is limited and under certain circumstances in highly degenerated tissues no vital cells are left. Moreover, the extraction of these cells is connected with additional surgery; also the expansion in vitro is difficult. Other approaches avoid these problems by using allo- or even xenogenic cells. These cells are more stable concerning their therapeutic behavior and can be produced in stock. To prevent an immune response caused by these cells, cell encapsulation (e.g. with alginate) can be performed. Certain studies showed that encapsulated allo- and xenogenic cells achieve promising results in treatment of several diseases. At this, stem cells, especially mesenchymal stem cells, are an interesting cell source for cell therapy approaches. This review deals on the one hand with cell therapy of encapsulated cells with focus on the use of stem cells and on the other hand with bioreactor systems for the expansion and differentiation of mesenchymal stem cells in reproducible and sufficient amounts for potential clinical use.
Keywords: Encapsulation; Stem cells; Cell therapy